Raloxifene as an Adjuvant Therapy for Patients With Schizophrenia: An Up‐To‐Date Systematic Review and Meta‐Analysis - Tzu‐Rong Peng; Hung‐Hong Lin; Jian‐Ying Wang; Ming‐Chia Lee; Shih‐Ming Chen (Brain and Behavior)
Abstract Background and Hypothesis Raloxifene may be useful as an adjunctive treatment for schizophrenia, particularly in addressing psychotic symptoms. This meta‐analysis aimed to evaluate the effectiveness and safety of adjunctive raloxifene in improving positive, negative, and general psychopathology symptoms, as measured by the Positive and Negative Syndrome Scale (PANSS). Study Design A systematic search was performed using PubMed, Embase, and the Cochrane Library databases for articles published until May 2024. Randomized controlled trials investigating the effectiveness and safety of adjunctive raloxifene for treating schizophrenia were included. The primary outcome was psychotic symptom severity using PANSS subscales. Mean differences (MDs) and their 95% confidence intervals (CIs) were calculated using random effects models. Study Results Ten studies were included in the final analysis. Compared with the placebo group, raloxifene as an adjunctive therapy significantly improved the positive, negative, general, and total PANSS scores, MD = −1.00 (95% CI = −2.00 to −0.20; I2 = 48%; p = 0.02; τ2 = 0.87), MD = −1.35 (95% CI = −2.74 to 0.04; I2 = 71%; p = 0.06; τ2 = 3.27), MD = −3.29 (95% CI = −5.74 to −0.83; I2 = 74%; p = 0.009; τ2 = 9.59), and MD = −7.12 (95% CI = −11.89 to −2.36; I2 = 74%; p = 0.003; τ2 = 41.86), respectively. Conclusions Adjunctive raloxifene appears to be a safe and effective treatment for improving positive, general, and total symptoms in patients with schizophrenia, particularly in those with mild‐to‐moderate illness and postmenopausal women. The 60 mg daily dose over at least 12 weeks yielded the most consistent benefits. Further high‐quality trials are needed to confirm its efficacy across diverse populations and guide personalized treatment strategies.